Assessment of concentrations of sTRAIL ligand and its receptors sTRAIL-R1 and sTRAIL-R2 – markers monitoring the course of the extrinsic pathway of apoptosis induction: potential application in ovarian cancer diagnostics - Aleksandra Mielczarek-Palacz; Justyna Sikora; Zdzisława Kondera-Anasz (Archives of Medical Science, 2015)
Introduction : TNF-related apoptosis-inducing ligand (TRAIL) together with its receptors are involved in activation of the extrinsic pathway of apoptosis. Due to the special role of the apoptosis pathway in pathogenesis of ovarian cancers, the aim of the study was to assess concentrations of sTRAIL, sTRAIL-R1 and sTRAIL-R2 in serum of affected women. Material and methods : The study group included 85 women with diagnosed ovarian tumors: 35 women with ovarian serous cystodenoma, 15 women with ovarian teratoma and 35 women with serous cystadenocarcinoma. The control group consisted of 30 healthy women. Concentrations of studied parameters were measured by ELISA methods. Results : Serum levels of all studied parameters were higher in serum of women with ovarian tumors than in the controls, but their concentrations varied depending on the clinical diagnosis. The highest concentration of TRAIL was found in serum of women with ovarian cancer, the highest sTRAIL-R1 level in serum of women with ovarian mature teratoma, and the highest sTRAIL-R2 level in serum of women with ovarian serous cystadenoma. Conclusions : The state of immunosuppression accompanying neoplastic disease depends on the extrinsic pathway of apoptosis induction in the TRAIL/TRAIL-R system. Determination of TRAIL-R1 and TRAIL-R2 levels may prove to be useful in ovarian tumor differential diagnostics, which requires further research.